Stable isotopes as tracers of copper corrosion in the atmosphere and soil environment: a geographic study on brochantite and malachite formations on historic and archaeological material using δ18O, δ13C and δ2H - Boos Pedroza, DA (2020)
A refined methodology using light stable isotopes in precipitation to determine the formation location of copper minerals is tested, for the eventual use on archaeological bronzes that corroded in the soil environment. To do this, δ18O in historic brochantite and archaeological malachite is used to determine whether the region in which these common minerals formed may be identified when the δ18O is a function of the δ18O in meteoric water and temperature. The waters in each phase of the hydrologic cycle have distinct isotopic compositions and can yield information on climate or water provenance. The possibility that this δ18O study can be supplemented by including the hydroxyl-δ2H in brochantite or δ13C in malachite is explored as sub-studies.